The unintended consequences of bundled payments. - Weeks, Bill; Rauh, Stephen S.; Wadsworth, Eric B.; Weinstein, James (Annals of Internal Medicine, 2012)
Consensus is building that episode-based bundled payments can produce substantial Medicare savings, and the Center for Medicare & Medicaid Innovation's Bundled Payment Initiative endorses this conc...